CANVAS Syndrome: A Comprehensive Case Report on Rare Ataxia - Evlyne Erlyana Suryawijaya; Ni Nengah Rida Ariarini; Freddy Sitorus; Eva Dewati; Dinda Diafiri (Lumina : Indonesian Journal of Neurology, 2025)
Introduction: Cerebellar ataxia with neuropathy and vestibular areflexia syndrome (CANVAS) is characterized by cerebellum, vestibular system, and sensory pathways impairments. It progresses slowly compared to other ataxias like Friedreich’s ataxia, and its genetic basis is complex and under investigation. Case Report: A 34-year-old male presented with worsening imbalance over the past year, vertigo, slurred speech, and hand tremors. Physical examination revealed bidirectional nystagmus, dysmetria, and cerebellar atrophy on MRI. Vestibular tests were abnormal, and neuropsychological assessments showed memory and executive function deficits. Sensory nerve conduction studies were normal. Discussion: The patient's symptoms of ataxia, vestibular areflexia, and sensory neuropathy are consistent with CANVAS. Cerebellar atrophy and Purkinje cell degeneration contribute to motor coordination deficits. Sensory neuropathy involves dorsal root ganglia degeneration. Despite supportive clinical features, genetic testing is necessary to confirm the diagnosis and exclude other genetic ataxias. Conclusion: CANVAS is a rare ataxia syndrome with autosomal recessive inheritance affecting the cerebellum, vestibular, and sensory systems. The patient's symptoms and MRI findings suggest CANVAS, but further genetic testing is required for definitive diagnosis.